Clinical Differences Between Single and Multiple Suicide Attempters, Suicide Ideators, and Non-suicidal Inpatients - Berardelli, Isabella; Forte, Alberto; Innamorati, Marco; Imbastaro, Benedetta; Montalbani, Benedetta; Sarubbi, Salvatore; De Luca, Gabriele Pasquale; Mastrangelo, Martina; Anibaldi, Gaia; Rogante, Elena; Lester, David; Erbuto, Denise; et al. (Frontiers in Psychiatry, 2020)
Single suicide attempters (SSAs) and multiple suicide attempters (MSAs) represent distinct subgroups of individuals with specific risk factors and clinical characteristics. This retrospective study on a sample of 397 adult psychiatric inpatients analyzed the main sociodemographic and clinical differences between SSAs and MSAs and the possible differences between SSAs, MSAs, and psychiatric patients with and without suicidal ideation (SI). Clinical variables collected included psychiatric diagnoses (Mini International Neuropsychiatric Interview), presence of substance use, current suicide risk status (Columbia Suicide Severity Rating Scale), Clinical Global Impression at admission, Global Assessment of Functioning improvement between admission and discharge, age at onset of psychiatric illness, duration of untreated illness in years, number of hospitalizations in psychiatric settings, and lethality of the most severe suicide attempt. A multinomial logistic regression model with groups showed that MSAs had a higher lethality of their last suicide attempt as compared to SSAs. In addition, MSAs had distinct sociodemographic characteristics compared to both SSAs and patients with SI. Although the study was limited by the relatively small sample size and retrospective nature, the present results suggest that identifying MSAs could be useful in predicting suicide risk and designing ad hoc prevention strategies.